Octocorals from Costa Rica: The genus Pacifigorgia (Coelenterata: Octocorallia: Gorgoniidae) - Breedy, Odalisca; Guzman, Hector M. (Zootaxa, 2003)
Species of the genus Pacifigorgia are surveyed for the first time in the shallow Pacific seas off Costa Rica. They are identified and described with detailed illustrations. The main collection belongs to the Zoology Museum, University of Costa Rica. Most of this material has been collected by means of SCUBA. This regional account of Pacifigorgia includes four species that were previously described: P. adamsii, P. eximia, P. irene and P. stenobrochis, and another nine that are new species.